Skin repairing patch and preparation method thereof
By combining melt electrostatic direct writing technology in skin repair patches, PCL patch skeletons and 3D-Exo-containing hydrogel materials are prepared, the shortcomings of skin repair patches in the prior art in terms of biocompatibility, mechanical properties and degradability are solved, and the effect of efficient sustained release of exosomes and prolonging activity time is achieved.
Patent Information
- Application Number
- CN202411547261.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-11
AI Technical Summary
The existing skin repair patches have shortcomings in terms of biocompatibility, mechanical properties and degradability, making it difficult to reproduce the internal environment, and it is difficult to effectively delay the release of exosomes and prolong their activity time.
The polycaprolactone (PCL) patch skeleton was prepared by melt electrostatic direct writing technology, and the hydrogel material containing 3D-Exo was poured into the patch skeleton, cross-linked and cured to form a composite material with high biocompatibility and mechanical strength.
It achieves high biocompatibility and mechanical strength of skin repair patches, provides an ideal environment for cell attachment, proliferation and differentiation, effectively sustained release of exosomes, prolongs its activity time in wound treatment, and ensures its stability in complex bodily fluid environments.
Smart Images

Figure CN119587764A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a skin repair patch and a preparation method thereof. Background Art
[0002] The skin is an important barrier to protect the human body. How to repair acute and chronic skin wounds caused by burns, diabetes, trauma and other diseases has always been a difficult problem faced by plastic surgery. Existing technologies hope to solve the problem of skin wound repair through skin repair patches. Skin repair patches are a type of medical material specifically used for skin repair and reconstruction. Its raw materials include biomaterials, artificial materials, etc., and the specific choice depends on the patient's specific situation and repair needs. In the past, the preparation of skin repair patches mainly relied on animal dermis (biomaterials), which still had many shortcomings in terms of biocompatibility, mechanical properties and degradability.
[0003] Melt Electrowriting (MEW) is an advanced micro-nano additive manufacturing technology that can precisely control the deposition position and shape of materials and is widely used in the fields of tissue engineering and regenerative medicine. In recent years, with the increasing demand for skin repair, the preparation of skin repair patches with artificial materials based on MEW technology has gradually become a research hotspot. However, clinical tests have shown that most of the prepared skin repair patches still have many shortcomings. Although they can expand the cell attachment area, it is difficult to reproduce the in vivo environment. Summary of the invention
[0004] The purpose of the present invention is to disclose a skin repair patch and a preparation method thereof, so as to solve one or more technical problems existing in the prior art and provide at least one beneficial option or create conditions.
[0005] The first aspect of the present invention is to provide a skin repair patch containing 3D-Exo.
[0006] The second aspect of the present invention is to provide a method for preparing the skin repair patch described in the first aspect of the present invention.
[0007] The skin repair patch described in the first aspect of the present invention includes a patch skeleton and a hydrogel material filled in the patch skeleton, wherein the raw material of the patch skeleton is polycaprolactone (PCL), and the hydrogel material contains 3D-Exo, which is an exosome obtained by a three-dimensional culture method.
[0008] The hydrogel material containing the 3D-Exo is combined with a PCL patch skeleton to form a composite material with high biocompatibility and mechanical strength. This composite material can provide an ideal cell attachment, proliferation and differentiation environment, while effectively releasing exosomes and prolonging the activity time of exosomes.
[0009] According to a preferred embodiment of the present invention, the preparation method of the 3D-Exo comprises the steps of: 1) using sodium alginate solution as a shell fluid and adipose stem cell suspension as a core fluid, extruding them into a CaCl2 solution by a coaxial extrusion device, and solidifying and forming them into a three-dimensional culture carrier; 2) rinsing the three-dimensional culture carrier with a sodium chloride solution, adding culture medium, and incubating at 37°C and 5% CO2; 3) separating the 3D-Exo from the three-dimensional culture carrier after incubation by sequential high-speed centrifugation.
[0010] The 3D-Exo is a nano-scale vesicle secreted by stem cells cultured in a three-dimensional culture carrier, which is rich in bioactive substances such as proteins and nucleic acids. It plays an important role in intercellular communication and regulation, and helps promote skin repair and regeneration.
[0011] According to a preferred embodiment of the present invention, the sequential high-speed centrifugation treatment process of step 3) is as follows: 3-1) the three-dimensional culture carrier is centrifuged at 300×g for 10 minutes, and then at 2000×g for 30 minutes to remove the precipitate; 3-2) the supernatant retained in step 3-1) is centrifuged at 10,000×g for 30 minutes, filtered through a 0.22 μm filter, and the filtrate is collected; 3-3) the filtrate obtained in step 3-2) is centrifuged at 100,000×g for 70 to 80 minutes, the precipitate is collected, and washed with PBS; 3-4) the precipitate obtained in step 3-3) is centrifuged at 100,000×g for 70 minutes, and the precipitate is collected and resuspended to obtain the 3D-Exo.
[0012] Since the three-dimensional culture carrier provides stem cells with a culture condition similar to the natural environment, it not only increases the production of exosomes, but also enhances the biological function of exosomes. Therefore, a more suitable separation method is needed to completely separate and purify the 3D-Exo.
[0013] According to a preferred embodiment of the present invention, the raw material of the hydrogel material includes methacrylic anhydride gelatin (GelMa). GelMa is a hydrogel derived from gelatin, which has good biocompatibility and adjustable physical properties. As an exosome carrier, GelMa hydrogel can slowly release 3D-exo; it simulates the extracellular matrix and moist environment for skin repair patches, which is conducive to cell attachment and proliferation.
[0014] According to a preferred embodiment of the present invention, the preparation method of the hydrogel material is: dissolving methacrylic anhydride gelatin and a photoinitiator in a PBS buffer solution, stirring at 40-55°C for 3 hours, cooling to 35-45°C, adding the 3D-Exo and stirring evenly, and removing bubbles by negative pressure to obtain the hydrogel material. The concentration of GelMa also has an important influence on the mechanical properties and biocompatibility of the hydrogel material. The concentration needs to be adjusted between 5 and 15% to ensure that it has sufficient mechanical strength and suitable viscosity and rheological properties for printing, but is not too dense to affect cell migration and exosome release. The preferred GelMa gelling concentration is 9-11%.
[0015] According to a preferred embodiment of the present invention, the porosity of the patch skeleton is 60-70%. The porosity of the patch skeleton determines the mechanical strength of the fiber membrane and its ability to combine with the hydrogel material. Too high a porosity not only cannot carry the cast hydrogel material, but also its mechanical strength and durability cannot meet the function of the skeleton; while too low a porosity makes it unable to carry enough of the hydrogel material and affects its effect in wound healing, and its flexibility and elasticity will be affected.
[0016] According to a preferred embodiment of the present invention, the thickness of the patch skeleton is 1±0.1 mm. The thickness affects the mechanical strength of the patch skeleton, the volume of the hydrogel material inside, and the portability of the skin repair patch.
[0017] The preparation method described in the first aspect of the present invention is to use molten electrostatic direct writing technology to additively prepare the patch skeleton, infuse the hydrogel material into the patch skeleton, and cross-link and solidify it into shape.
[0018] Although the hydrogel material loaded with the 3D-Exo has good biocompatibility, its mechanical strength is relatively low and may not meet the requirements of specific tissue engineering for the supporting structure. However, when combined with the PCL patch skeleton prepared by MEW technology, the prepared skin repair patch has both the mechanical strength of PCL and the high water content and biocompatibility of GelMa, which can effectively release exosomes, prolong their activity time in wound treatment, and ensure their stability in a complex body fluid environment.
[0019] According to a preferred embodiment of the present invention, the molten electrostatic direct writing technology uses a metal nozzle with a 23G needle.
[0020] According to a preferred embodiment of the present invention, the fused electrostatic direct writing technology printing process is carried out at an ambient temperature of 23±2° C. and a relative humidity of 50±1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a picture characterizing the 3D-Exo in Example 1; Figure 2 This is a graph showing the detection results of 3D-Exo on cell proliferation and migration abilities described in Example 2; Figure 3 This is a graph showing the detection results of the in vitro effects of 3D-Exo on cells described in Example 2; Figure 4 is a picture characterizing the skin repair patch in Example 4; Figure 5 is a graph of exosome release from skin repair patches with different porosities in Example 5; Figure 6 is a picture of the wound treatment comparison experiment in Example 6; Figure 7 is a histological analysis picture of the wound site after treatment in Example 6; Figure 8 is a picture of collagen regeneration analyzed by Masson trichrome staining in Example 6; Fig. 9 is a picture of the analysis of collagen regeneration and angiogenesis by immunostaining in Example 6; Fig.10 This is a Western blot of the expression level of type III collagen in Example 6. DETAILED DESCRIPTION
[0022] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all belong to the scope of the present invention.
[0023] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
[0024] The molecular biology experimental methods not specifically described in the following examples are all carried out with reference to the Molecular Cloning Experiment Guide (3rd edition) or in accordance with the kits and product instructions; the biological materials of the kits, unless otherwise specified, can be obtained from commercial channels.
[0025] Example 1: Acquisition of 3D-Exo (1) Cultivation of human adipose-derived stem cells (ADSCs).
[0026] Human adipose-derived stem cells were placed in a 150 mm cell culture dish, 25-30 mL of MSC culture medium (7521, Sciencell, USA) was added, and cultured at 37°C and 5% CO2.
[0027] (2) Preparation and cultivation of three-dimensional culture carriers.
[0028] The ADSCs suspension prepared above was used as the core fluid, and a sodium alginate solution with a concentration of 1.5-3% was used as the shell fluid. The solution was extruded into a CaCl2 solution with a concentration of 3-4% by a coaxial extrusion device for gelation to form a three-dimensional culture carrier with an outer gel encapsulating the inner cell suspension. The three-dimensional culture carrier was rinsed three times with a sodium chloride solution with a concentration of 0.9%, transferred to a new culture dish, and MSC conditioned medium (NC0103, Yocon, China) was added and incubated at 37°C and 5% CO2.
[0029] (3) Isolation of exosomes.
[0030] The MSC conditioned medium collected for culturing the three-dimensional culture carrier was subjected to sequential centrifugation and filtration, first at 300×g for 10 minutes to precipitate intact cells, and then at 2000×g for 30 minutes to precipitate dead cells. The partially purified medium from which cells and cell debris were removed was then centrifuged at 10,000×g for 30 minutes. The supernatant was filtered through a 0.22 μm filter to remove vesicles or protein aggregates. Next, the supernatant was centrifuged at 100,000×g for 70 to 80 minutes. The resulting precipitate was washed with PBS, transferred to a new tube, and centrifuged at 100,000×g for 70 minutes. The 3D-Exo was obtained.
[0031] All centrifugations were performed at 4°C using a benchtop ultracentrifuge.
[0032] (4) Characterization and internalization experiments of the 3D-Exo.
[0033] The morphology and microstructure of the 3D-Exo were examined by transmission electron microscopy (TEM). Figure 1 As shown in Figure a, TEM analysis showed that the collected 3D-Exo was cup-shaped or spherical. Nanosight analysis was used to evaluate the particle size distribution and particle concentration of ADSC-Exo. Figure 1 As shown in b. The results of Western blot are shown in Figure 1 As shown in c, the 3D-Exo expressed TSG101 and CD81, characteristic surface markers of exosomes.
[0034] To test whether human umbilical vein endothelial cells (HUVECs) (Procell, China) could take up the 3D-Exo, the 3D-Exo was incubated with a red fluorescent dye (PKH26, fluorescence, China) for 5 minutes, and then the excess dye was removed with 0.5% BSA / PBS. Subsequently, the residual dye was further removed by centrifugation to obtain the labeled 3D-Exo. HUVECs were seeded in a confocal dish and treated with labeled 3D-Exo. After 24 hours of incubation, the cells were washed with PBS. Subsequently, the cells were fixed with 4% paraformaldehyde for 15 minutes and washed again with PBS. FITC phalloidin (Yeasen Biotech Co., China) and DAPI (Solarbio, China) were used to stain the cytoskeleton and cell nucleus, respectively. After 24 hours of incubation, a large number of PKH26-labeled exosomes were found to be concentrated in the perinuclear region of the cells (such as Figure 1 (shown in middle d), indicating that the 3D-Exo were rapidly internalized by HUVECs.
[0035] Example 2: 3D-Exo and 2D-Exo control experiment In vitro tests were performed to evaluate the advantages and disadvantages of exosomes (3D-Exo) obtained by three-dimensional culture methods and exosomes (hereinafter referred to as 2D-Exo) obtained by planar (two-dimensional) culture methods.
[0036] (1) Preparation of 2D-Exo.
[0037] About 1.5×10 6 ADSCs were inoculated into a culture dish and cultured to 60-80% confluence, rinsed two to three times with PBS buffer (Gibco, USA), each for 5 minutes, and then the culture medium was replaced with MSC conditioned medium (NC0103, Yocon, China). Then, the exosomes were separated and purified according to the exosome separation method provided in Example 1.
[0038] (2) The effects of 2D-Exo and 3D-Exo were tested on human immortalized keratinocytes (HaCaT) and human umbilical vein endothelial cells (HUVECs), respectively.
[0039] According to the characterization and internalization experimental methods provided in Example 1, the differences between 2D-Exo and 3D-Exo were compared in vitro. Figure 2 As shown, 3D-Exo has significant advantages in promoting cell proliferation and migration compared with 2D-Exo.
[0040] (3) HUVECs and HaCaT (Procell, China) were cultured in Dulbecco’s modified Eagle’s medium (DMEM) containing 10% fetal bovine serum (Gibco) and 1% penicillin-streptomycin (Gibco) at 37°C and 5% CO2.
[0041] HUVECs and HaCaT cells were cultured at 2×10 3 Cells were seeded at a density of 1×10 cells / well in a 96-well culture plate, and 100 μL of the above cell culture medium was added to each well. 8 Particles / mL, 2.5×10 8 particles / mL and 5×10 8 Cells were stimulated with 3D-Exo particles / mL for 1, 2, or 3 days. Cell proliferation was detected using a cell counting kit-8 (Sigma), and the absorbance of the culture medium was measured at 450 nm using a multilabel labelcounter (n = 3).
[0042] like Figure 3 As shown in a and b, after 48 hours of incubation, the proliferation of HUVECs and HaCaT cells was significantly enhanced in a dose-dependent manner under the action of 3D-Exo compared with the control group, and the amount of proliferation increased with the increase of exosome concentration.
[0043] (4) Tube formation experiments were performed using the Matrigel method. 4 HUVECs were seeded on Matrigel (BD, 356234) in a 96-well plate and 1×10 8 Particles / mL, 2.5×10 8 particles / mL and 5×10 8 Pellets / mL3D-Exo or DMEM (control) were incubated. Tube formation was observed after 8 h. The number of grids, number of major branches, number of major nodes, and total major branch length were measured using ImageJ (NIH, Bethesda, MD).
[0044] from Figure 3 As can be seen in Figure c, the tube-forming ability of HUVECs in the group loaded with 3D-Exo was significantly improved compared with the control group. 9 / mL 3D-Exo treatment group showed the most significant effect in promoting angiogenesis. In addition, this group showed an increase in the number of angiogenesis, as manifested by an increase in the number of nodes and branches. Based on these experimental results, we concluded that at 1×10 9 At a concentration of 1.34 × 10 / mL, 3D-Exo showed good cytocompatibility and clear stimulatory effect on angiogenesis.
[0045] (5) Cell migration assay.
[0046] HUVECs and HaCaT cells were cultured at 5 × 10 5 Cells were seeded into 6-well plates at a density of 10 cells / well and cultured to 100% confluence. The cell surface was scraped with a 200 μL pipette tip and washed twice with PBS buffer to remove free cells. 8 Particles / mL, 2.5×10 8 particles / mL and 5×10 8 Particles / mL3D-ADSC-Exos stimulated cells. The scratched area was observed and photographed at 0, 24, and 48 hours, and measured using ImageJ software.
[0047] Before scratching, each group was treated with PBS or different concentrations of 3D-Exos for 24 hours. The results showed that at two time points (24 hours and 48 hours), the cell healing rate in the 3D-Exo-treated group was significantly higher than that in the other groups. As the concentration of exosomes increased, the number of migrated cells in each field of view gradually increased, indicating that 3D-Exo has a promoting effect on the migration of HaCaT and HUVECs (e.g. Figure 3 The results of the migration experiment are consistent with the trend of the CCK-8 experiment. Therefore, 1×10 9 The 3D-Exo concentration of 1000 μg / mL was used as the final combination for subsequent experiments.
[0048] Example 3: Preparation of skin repair patch (1) Printing of the patch skeleton.
[0049] The molten electrostatic writing (MEW) equipment includes a metal nozzle, a metal collector, a high-voltage power supply and a 3D bioprinter. The polycaprolactone (PCL) material was loaded into the hopper of the 3D bioprinter. A metal nozzle with a 23G needle was used. The hopper temperature was set to 100°C and the metal collector temperature was set to 10°C. A negative current was applied through the needle grounding at a pressure of 0.2 MPa. The distance between the metal collector and the metal nozzle was set to 2~3 mm, and the voltage was set to 1~3 kV. The porosity of the print was set to 80%, and 100 layers were printed. The printing process was carried out at an ambient temperature of 23±2°C and a relative humidity of 50±1%. After about one hour, a 1 mm thick nanofiber membrane was formed on the collector. The fiber membrane was washed with high-purity water and dried at 35~40°C to obtain the patch skeleton.
[0050] (2) Preparation of hydrogel materials.
[0051] 1 g of methacrylic anhydride gelatin (GelMa) and 0.05 g of photoinitiator (LAP) were dissolved in 5 mL of PBS solution and stirred at 40-55°C for 3 hours. Then, the temperature of GelMa was controlled to 35-45°C and 5 mL of PBS solution containing the 3D-Exo was added to the mixture at a stirring speed of 100-200 rpm. The mixture was placed in a vacuum machine, the air pressure was set to -0.1 MPa, and the vacuum degassing time was 10-30 minutes. The final GelMa gel concentration of the hydrogel material was controlled to be 9-11%.
[0052] (3) Pouring and curing.
[0053] The temperature of the hydrogel material was controlled to 23°C, and the patch skeleton was placed on a metal collector with the platform temperature set to 10°C. The hydrogel material was evenly poured onto the patch skeleton and allowed to spread freely and penetrate into the pores of the patch skeleton. When the temperature of the hydrogel material dropped below 20°C, the fluidity decreased. The wavelength used was 405 nm and the intensity was 100 mw / cm 2 The hydrogel material is photocured by blue light, and the cross-linking time is controlled to be 40 to 70 seconds. After curing, the skin repair patch is obtained.
[0054] Example 4: Characterization of Skin Repair Patch (1) The surface morphology and structure of the skin repair patch were evaluated by scanning electron microscopy (SEM, ZEISS).
[0055] Scanning electron microscope (SEM) images show that the skin repair patch has a uniform pore distribution with an average pore size of 300-400 μm. Figure 4 As shown in a and b in the figure. It is worth noting that the hydrogel material exhibits a relatively smooth surface and an interconnected porous structure, which can be observed from the SEM images. Figure 4 In b, it can be seen that the fiber structure of the patch skeleton is evenly distributed and embedded in the hydrogel material structure. In addition, all pores in the patch skeleton are filled with the hydrogel material without affecting the morphology and fiber arrangement of the patch skeleton. This unique structure improves the water absorption capacity of the skin repair patch, enabling effective penetration from the wound while maintaining a moist microenvironment.
[0056] (2) Soak the freeze-dried skin repair patch in distilled water or PBS at room temperature for 24 hours until the swelling equilibrium state is reached.
[0057] The swelling degree is calculated by the following formula: Swelling degree = (weight after swelling - dry weight) / dry weight × 100%. The moisturizing ability of the skin repair patch is evaluated by the same method. After the skin repair patch reaches a swelling equilibrium state, the swollen skin repair patch is placed in a desiccator at room temperature, and the swelling change is measured every 3 hours.
[0058] The skin repair patch exhibits excellent swelling ability. Figure 4 The swelling behavior of the skin repair patch in water or PBS is shown in Figure c. After 24 hours of immersion, the swelling rate reaches an astonishing 603%.
[0059] (3) Controlled release of 3D-Exo by the skin repair patch.
[0060] The skin repair patch of appropriate size was placed in the transmembrane upper chamber of a 24-well plate at 37°C, and 100 µL of dPBS solution was placed in the lower chamber. The liquid in the lower chamber was removed at 0.5, 1, 2, 3, 4, 5, 6, and 7 days. The protein concentration of the liquid in the lower chamber was quantified using the BCA method, and the percentage of released exosomes was calculated.
[0061] The release curve of the exosomes loaded in the skin repair patch is as follows Figure 4 As shown in (d) in the middle, the cumulative release exceeded 71% after 7 days.
[0062] (4) Cytotoxicity test.
[0063] To further evaluate the cytotoxicity of the skin repair patch and assess its effect on cell growth, HUVECs were co-incubated with the skin repair patch for 48 hours. Figure 4 As shown in Figure e, the cells within the skin repair patch are intact and the cellular processes are freely extending.
[0064] (5) Cell adhesion test.
[0065] In the process of preparing the skin repair patch, the patch skeleton was cut into a size suitable for a 24-well plate, disinfected with 75% ethanol, and photocured after adding the hydrogel material. After being rinsed twice with PBS solution, the patch was washed with 5×10 4 Cells were seeded at a density of 1:1 / well. After 2 days of incubation, the supernatant was aspirated and the cells were treated with a Calcein / PI cell viability / cytotoxicity assay kit (Beyotime, China). Cells attached to the skin repair patch were observed and photographed using an inverted fluorescence microscope.
[0066] After removal of the hydrogel, it was observed that cells seeded on the skin repair patch were able to firmly attach and grow along the aligned fibers (e.g. Figure 4(f) Notably, cell growth showed a network pattern consistent with fiber alignment. The printing strategy of the skin repair patch provides an ideal microenvironment for promoting cell adhesion and guiding directional cell growth.
[0067] Example 5: Skin repair patch parameter optimization experiment Since the porosity determines the mechanical strength of the fiber membrane and its ability to combine with the hydrogel material, it is expected that a suitable porosity can be selected through optimization experiments to obtain good mechanical strength, durability, flexibility and drug sustained release effect.
[0068] According to the preparation method provided in Example 3, skin repair patches with porosities of 50%, 60%, 70%, 80% and 90% were prepared for sustained release experiments. The experiment was carried out according to the method provided in "(3) Controlled release of 3D-Exo by the skin repair patch" in Example 4. The results are as follows Figure 5 As shown in the figure, it can be found that the release curve of exosomes is smoother when the porosity is 70%, and the release amount reaches 79% on the 14th day; the release amount corresponding to 50% porosity is 80%, the release amount corresponding to 60% porosity is also 80%, the release amount corresponding to 80% porosity is 73%, and the release amount corresponding to 90% porosity is 67%.
[0069] The skin repair patch with a porosity of 50% feels thicker and will appear hollow when it fits the body curve. After comprehensive consideration, the skin repair patch with a porosity of 60-70% can release a certain amount of exosomes to fight inflammation in the early stage while maintaining a certain mechanical strength, and can release more exosomes to promote angiogenesis and collagen remodeling in the later stage, which is more in line with the mechanism of promoting wound healing. Therefore, the optimal porosity is 60-70%.
[0070] Example 6: Effect of using the skin repair patch (1) Skin repair patches promote wound healing.
[0071] To study the effect of promoting wound healing in vivo, full-thickness skin wounds were created on the backs of mice, and skin repair patches (Exosome / PG group), blank dressings (PG group) or no treatment (control group) were used. The blank dressing refers to the process of preparing the skin repair patch without adding 3D-Exo. Figure 5The appearance of the wound at different time points is shown in a in the middle. Visual observation showed that there was no infection at the wound site of the mice during the experiment. The wounds of all groups were significantly reduced after 7 days of treatment, and the skin repair patch group healed the fastest. The skin repair patch group showed the best wound closure speed and the most effective healing effect. The wound was almost completely closed at 14 days, while the other two groups still had unhealed wounds. The control group had the largest unhealed area (wound closure efficiency is shown in Figure 5 As shown in b). Due to the suitable moisturizing ability and unique biocompatibility of the skin repair patch group, it also showed a good wound healing promoting effect, which indicates that the skin repair patch has potential as a wound covering material.
[0072] (2) Histological analysis of wound healing.
[0073] During wound healing, exosomes induce cell proliferation and differentiation around the wound through paracrine signaling pathways, promoting tissue repair. Angiogenesis and epithelial regeneration occur simultaneously in this process. HE staining shows epithelial regeneration in the wound area. Figure 6 As shown in a, the skin repair patch significantly enhanced the epithelial regeneration of the wound defect on the 14th day after surgery compared with the control group and the blank dressing group. In addition, the epidermis of the new granulation tissue in the skin repair patch and blank dressing groups was intact and thick. In the control group, the epidermal structure was not integrated, and there was only a thin dermis. The wounds in the blank dressing group and the skin repair patch group showed thicker epidermal formation, indicating that it may have a stimulating effect on the migration and proliferation of epithelial cells.
[0074] To examine the formation of skin appendages (including hair follicles and sebaceous glands) during wound healing, histological sections of the skin at the wound site were taken on day 21 (e.g. Figure 6 (shown in b). Although all three groups completed epithelial regeneration and formed new skin, the scar healing area in the skin repair patch group was smaller than that in the other two groups. In addition, the new epidermis in the skin repair patch group appeared smooth and uniform, with a tight connection between the epidermis and the dermis, similar to the normal tissue morphology. In contrast, the new epidermis in the other two groups showed different thicknesses and different cell arrangements.
[0075] (3) Skin repair patches enhance extracellular matrix (ECM) deposition during the healing process.
[0076] Proper collagen deposition and remodeling can enhance the tensile strength of the tissue and improve healing. Masson's trichrome staining is used to assess collagen deposition and maturation. Figure 7 Masson trichrome-stained sections at day 14 and day 21 are shown in a and b in the figure. Figure 7As shown in a, Masson staining revealed collagen deposition in the wounds of different groups, with the skin repair patch group showing the largest collagen-positive area. On days 14 and 21, new collagen was increased in all groups. The collagen deposition on the wound bed in the skin repair patch group was relatively denser and more continuous, which was more obvious than in the other two groups. Semi-quantitative analysis of collagen deposition (see Figure 7 (B) showed that on the 14th and 21st days, the collagen content in the skin repair patch group was significantly higher than that in the control group and the blank dressing group.
[0077] The results of type III collagen immunostaining on day 14 were as follows Figure 8 As shown in a, it shows a similar trend to Masson trichrome staining. As the healing time progresses, the deposition of type III collagen in all groups increases, with the skin repair patch group having the highest intensity on day 14 (quantitative results are shown in Figure 8 This result is consistent with the western blot result of type III collagen (see Fig. 9 ). Combined with the results of Masson staining and immunohistochemical staining, these findings suggest that wounds treated with the skin repair patch effectively enhanced the epithelial regeneration process and collagen deposition, leading to improved healing outcomes.
[0078] (4) Skin repair patches enhance angiogenesis in vivo.
[0079] Angiogenesis plays a vital role in wound repair because the newly formed vasculature facilitates gas exchange, nutrient transport, and metabolism, which are necessary for complete healing. CD31 immunohistochemical staining was performed to detect angiogenesis in skin tissue (e.g. Figure 8 As shown in b in the figure). It can be observed from the figure that the newly formed blood vessels in each group are clearly visible. The quantitative analysis of the blood vessels marked in the CD31 staining image showed that the angiogenesis in the skin repair patch group increased significantly, which was significantly higher than that in the skin repair patch group and the control group (the quantitative analysis results are shown in Figure 8 These results suggest that the skin repair patch enhanced wound vascularization and promoted wound healing.
[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A skin repair patch, characterized in that: It includes a patch skeleton and a hydrogel material filled in the patch skeleton. The raw material of the patch skeleton is polycaprolactone. The hydrogel material contains 3D-Exo, which is an exosome obtained by a three-dimensional culture method.
2. The skin repair patch according to claim 1, characterized in that: The preparation method of 3D-Exo comprises the steps of: 1) Sodium alginate solution is used as the shell fluid and adipose stem cell suspension is used as the core fluid. The alginate solution is extruded into a CaCl2 solution by a coaxial extrusion device and solidified into a three-dimensional culture carrier. 2) washing the three-dimensional culture carrier with a sodium chloride solution, adding a culture medium, and incubating at 37° C. and 5% CO 2 ; 3) The three-dimensional culture carrier that has completed incubation is subjected to sequential high-speed centrifugation to separate the 3D-Exo.
3. The skin repair patch according to claim 2, characterized in that: Step 3) The processing flow of the sequential high-speed centrifugation is as follows: 3-1) The three-dimensional culture carrier is centrifuged at 300×g for 10 minutes and then at 2000×g for 30 minutes to remove the precipitate; 3-2) The supernatant retained in step 3-1) was centrifuged at 10,000 × g for 30 minutes, filtered through a 0.22 μm filter, and the filtrate was collected; 3-3) The filtrate obtained in step 3-2) was centrifuged at 100,000×g for 70-80 minutes, and the precipitate was collected and washed with PBS; 3-4) The precipitate obtained in step 3-3) is centrifuged at 100,000×g for 70 minutes, and the precipitate is collected and resuspended to obtain the 3D-Exo.
4. The skin repair patch according to any one of claims 1 to 3, characterized in that: The raw material of the hydrogel material includes methacrylic anhydride gelatin.
5. The skin repair patch according to claim 4, characterized in that: The preparation method of the hydrogel material is as follows: dissolving methacrylic anhydride gelatin and a photoinitiator in a PBS buffer solution, stirring at 40-55° C. for 3 hours, cooling to 35-45° C., adding the 3D-Exo and stirring evenly, and removing bubbles under negative pressure to obtain the hydrogel material.
6. The skin repair patch according to claim 1, characterized in that: The porosity of the patch skeleton is 60-70%.
7. The skin repair patch according to claim 1, characterized in that: The thickness of the patch skeleton is 1±0.1 mm.
8. The method for preparing the skin repair patch according to claim 1, characterized in that: The patch skeleton is prepared by additive manufacturing using a melt electrostatic direct writing technique, and the hydrogel material is poured into the patch skeleton for cross-linking and curing.
9. The preparation method according to claim 8, characterized in that: The fused electrostatic direct writing technique uses a metal nozzle with a 23G needle.
10. The preparation method according to claim 8, characterized in that: The fused electrostatic direct writing printing process is carried out at an ambient temperature of 23±2° C. and a relative humidity of 50±1%.